Rationality as a barrier to peace: micro-evidence from Kosovo - Sumon Kumar Bhaumik; Ira N. Gang; Myeong-Su Yun (Institute for the Study of Labor (IZA), 2007)
Despite a significant expansion of the literature on conflicts and fragility of states, only a few systematic attempts have been made to link the theoretical literature on social conflicts to the available micro-level information about the people who are involved in these conflicts. We address this lacuna in the literature using a household-level data set from Kosovo. Our analysis suggests that it is individually rational for competing ethnic communities, Kosovo Albanians and Kosovo Serbs, to resist a quick agreement on a social contract to share the region's resources.
urn:nbn:de:101:1-2008041485
Keywords: 330; Sozialer Konflikt; Ethnische Beziehungen; Rationales Verhalten; Sozialvertrag; Friedenssicherung; Kosovo